Research Trends In Preeclampsia Between 1985-2013 In Perú: A Bibliometric Study - Huertas, Oscar Huapaya (2019)
Objective. The aim of the study is to characterize the national scientific production in preeclampsia during the period 1985-2013. Marerials and Methods. Bibliometric analysis of scienfic articles about preeclampsia in Peru. A search of journals indexed on PubMed, SciELO and LILACS from 1985 until July 2013. Original articles and those which have been done entirely in Peru were selected.